Drivers and consequences of tenure insecurity and mechanisms for enhancing tenure security: A synthesis of CGIAR research on tenure security (2013-2020) - McLain, Rebecca (International Food Policy Research Institute, 2021)
Research since the 1990s highlights the importance of tenure rights for sustainable natural resource management, and for alleviating poverty and enhancing nutrition and food security for the 3.14 billion rural inhabitants of less-developed countries who rely on forests and agriculture for their livelihoods. Which rights or combination of rights an individual, household, or community has affects whether they have access to land and resources, as well as how those can be used and for how long. Equally important is the degree to which landholders perceive their tenure to be secure. Landowners are more likely to engage in land and resource conservation if they perceive that the likelihood of losing their land or resource rights is low. Between 2013 and 2021, the CGIAR Research Program on Policies, Institutions, and Markets (PIM) supported researchers to explore the drivers of tenure insecurity and their consequences, as well as mechanisms that can enhance tenure security. Their work focused on rights held by individuals and households as well as collectively held rights. Studies found that tenure insecurity has a variety of negative consequences for natural resource management, agricultural productivity, and poverty reduction, but the sources of tenure insecurity differ for men and women, and for individual, household, and collective lands. Statutory recognition of customary rights, multistakeholder processes such as for land use planning, and organized social alliances such as Indigenous Peoples’ groups have emerged as important mechanisms for securing rights or enhancing access to collectively held lands. Long-term partnerships, ongoing engagement, and training for multiple actors at multiple scales increases the likelihood of successful implementation of tenure reforms. Further research on tenure security can contribute to achieving the Sustainable Development Goals, especially by clarifying how customary tenure can provide security and how tenure affects decision-making in multistakeholder platforms.